Lights in the Sky : Identifying and Understanding Astronomical and Meteorological Phenomena - Maunder, Michael ((Patrick Moore's Practical Astronomy Series))
Contenido: 1) Introducción; 2) Contaminación de la luz; 3) Contaminación del aire; 4) El clima; 5) El ojo humano; 6) El crepúsculo; 7) Luz del alba; 8) Luz del día; 9) Luz del anochecer; 10) Luz nocturna; 11) Resplandor; 12) Arco iris; 13) Relámpagos; 14) OVNI y visitantes alienígenas; 15) Rarezas.